Validation of the Borg Scale in Participants with Type 2 Diabetes Mellitus [Validación de la Escala de Borg en Personas Con Diabetes Mellitus Tipo 2 - Cofre-Bolados, C (Sociedad Medica de Santiago, 2016)
Background: Borg Rating of Perceived Exertion Scale (RPE) is a psychophysiological measurements that translates physical stimuli to a psychological construct, which is perceived exertion. Its use is simple and it represents the effort perception. Each number of the scale is associated with a heart rate or percentage of maximal oxygen consumption (VO2max), which estimates the intensity of exercise. Aim: To validate RPE scale in patients with type 2 diabetes mellitus (DM2). Material and Methods: Thirty five DM2 participants with a median age of 59 years underwent an incremental exercise test in a treadmill with breath-by-breath analysis of oxygen consumption. After every three minute stage, the RPE scale was applied and correlated with oxygen consumption variables. Results: There was correlation coefficient of 0.91 between RPE score and VO2max. A RPE score of 11 corresponded to 52% of VO2max, a RPE score of 13 corresponded to 76% of VO2max, a RPE of 15 corresponded to 88% of VO2max and a RPE of 17 correspondent to a 100% of VO2max. Conclusions: RPE Scale is valid in patients with type 2 diabetes as an estimate of the intensity of physical activity. © 2016, Sociedad Medica de Santiago. All rights reserved.